2008
DOI: 10.1088/0022-3727/41/17/175004
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic CrSb thicker films epitaxially grown on NaCl (1 0 0) substrates

Abstract: A series of relatively thicker CrSb films were deposited on NaCl (1 0 0) substrates by magnetron sputtering. Strong ferromagnetism was observed in the CrSb films with a zinc-blende CrSb (ZB-CrSb) phase epitaxially grown on the NaCl sustrate. The critical thickness of the ZB-CrSb film was close to 4 nm, which is sufficiently thick to investigate the half-metallicity nature of ZB-CrSb and to be practically applied in spintronics devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Half-metallicity arises as a result of interplay between the exchange splitting and the hybridization. Some Cr-based chalcogenides and pnictides, 17,[24][25][26][27][28][29][30][31][32][33][34] have been predicted to be not only HM but also potential candidates for possessing high Curie temperatures T c . Akinaga et al 24 have reported growing ZB thin films of CrAs on GaAs (001) substrates via molecular beam epitaxy.…”
Section: Half-metallic (Hm) Ferromagnetismmentioning
confidence: 99%
See 1 more Smart Citation
“…Half-metallicity arises as a result of interplay between the exchange splitting and the hybridization. Some Cr-based chalcogenides and pnictides, 17,[24][25][26][27][28][29][30][31][32][33][34] have been predicted to be not only HM but also potential candidates for possessing high Curie temperatures T c . Akinaga et al 24 have reported growing ZB thin films of CrAs on GaAs (001) substrates via molecular beam epitaxy.…”
Section: Half-metallic (Hm) Ferromagnetismmentioning
confidence: 99%
“…These showed ferromagnetic behavior at temperatures in excess of 400 K and magnetic moments of 3µ B per CrAs unit. Thin films of CrSb grown similarly on GaAs, (Al,Ga)Sb, and GaSb substrates have been found to be of ZB structure and ferromagnetic with T c higher than 400 K. 35 Deng et al 36 were successful in increasing the thickness of ZB-CrSb films to ∼ 3 nm using (In,Ga)As buffer layers, and Li et al 25 were able to grow ∼ 4 nm thick ZB-CrSb films on NaCl (100) substrates. Two of the present authors have recently presented an extensive theoretical study of the exchange interactions and Curie temperatures in a series of Cr-based pnictides and chalcogenides in ZB structure as a function of the lattice parameter.…”
Section: Half-metallic (Hm) Ferromagnetismmentioning
confidence: 99%
“…MnSb is ferromagnetic (FM) with a Curie temperature T C of 587 K. Half-metallic pnictides are especially promising since their SP at the Fermi energy may approach 100% [11][12][13]. While understanding the temperature dependence of their SP remains crucial to exploiting these materials in room-temperature devices [14], it is known that the surfaces [15] and interfaces [16,17] of half-metals may fail to show high SP even at cryogenic temperatures due to localized minority spin states.…”
Section: Introductionmentioning
confidence: 99%
“…Half-metallic ferromagnets with high (room temperature and above) Curie temperatures T c are ideal for spintronics applications, and as such, much experimental and theoretical [1][2][3] effort has been devoted in recent years to the designing of and search for such materials. Among these, Cr-doped dilute magnetic semiconductors (DMS) 4,5 or Cr-based alloys and in particular CrAs and CrSb [6][7][8][9][10][11][12][13][14][15][16] in Zinc Blende(ZB) structure have attracted particular attention, not only because of the possibility of complete spin polarization of the carriers at the Fermi level, but also for their possible high T c . Akinaga et al 6 were able to grow ZB thin films of CrAs on GaAs (001) substrates by molecular beam epitaxy, which showed ferromagnetic behavior at temperatures in excess of 400 K and magnetic moments of 3µ B per CrAs unit.…”
Section: Introductionmentioning
confidence: 99%
“…However, the possibility remains open that such difficulties will be overcome with progress in techniques of film-growth and materials preparation in general. Recently, Deng et al 23 were successful in increasing the thickness of ZB-CrSb films to ∼ 3 nm by molecular beam epitaxy using (In,Ga)As buffer layers, and Li et al 7 were able to grow ∼ 4 nm thick ZB-CrSb films on NaCl (100) substrates.…”
Section: Introductionmentioning
confidence: 99%